EXPERIMENTAL RESEARCHES OF DYNAMIC AND TRANSPORT PROPERTIES OF DUST STRUCTURES IN HIGH-FREQUENCY ARGON PLASMA - Dosbolayev, М.K.; Zhabayeva, B.S.; Orazbayev, S.A.; Ramazanov, T.S. (Хабаршы. Физика сериясы, 2018)
In this work the dependence of dynamical and transport properties of dust structures of high-frequency argon plasma as functions of a discharge power and a gas pressure, was experimentally investigated.